Comparative Study on Conventional and Ultrasound Irradiation Promoted Synthesis of 2,3-Disubstitutedquinoxaline Derivatives - Ahmed Mutanabbi Abdula; Ghazwan Ali Salman; Hamid H. Mohammed (Al-Mustansiriyah Journal of Science, 2018)
A series of ten chalcone-substituted quinoxalines (4a-e), (3a-e) starting from 1-(phenylquinoxalin-2-yl)ethanone and 1-(3-methylquinoxalin-2-yl)ethanone have been synthesized using conventional heating and ultrasound-assisted methods. Furthermore, novel of five quinoxaline derivatives including pyrazoline, isoxazole, pyrimidin-2-one, N-acylpyrazoline and pyridin-2-one moieties were also prepared from the reaction of chalcone compound 4a with different cyclization reagents using the same strategy. The structures of all synthesized compounds were established on the basis of FT-IR, 1H-NMR and 13C-NMR. The ultrasonic irradiation method provide several advantages over conventional heating method, including shorter reaction times (30-90 min.) and good percentage yields (65% - 88%), comparing with conventional protocol (5 to 20 hrs. with 30% to 55% reaction yields).